2004
DOI: 10.1051/forest:2003082
|View full text |Cite
|
Sign up to set email alerts
|

Relative efficiency of alternative methods to evaluate wood stiffness in the frame of hybrid larch (Larix�נeurolepis Henry) clonal selection

Abstract: -This study compares the efficiency of 3 indirect techniques that evaluate Young's modulus all along the sawing leading to the production of normalised specimens of hybrid larch trees from a clonal test. Ultrasonic speed is demonstrated as an interesting method for clone classification regarding Young's modulus in a clonal selection programme, whatever the sawing stage. However, the quality of results is reduced with standing tree measurements. The use of both the Pilodyn and resonance frequency measures is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
0
11
2
Order By: Relevance
“…The mean value ranged from 9.44 to 15.41 mm for Pilodyn penetration, 0.3514 to 0.4913 g.cm -3 for wood basic density and 3.94 to 7.53 GPa for MoE, which were smaller than previous studies on the same species Kien et al 2008;Wei et al 1997) as well as other species (Jacques 2004;Zhu et al 2008;Zhu et al 2009). The most suitable range of basic density for pulpwood in eucalyptus is 0.48 to 0.57 g • cm -3 and pulp yield decrease sharply when basic density falls below 0.4 exceeds 0.60 (Dean 1995;Ikemori et.…”
Section: Comparison Between Pilodyn Penetration and Wood Propertiescontrasting
confidence: 45%
“…The mean value ranged from 9.44 to 15.41 mm for Pilodyn penetration, 0.3514 to 0.4913 g.cm -3 for wood basic density and 3.94 to 7.53 GPa for MoE, which were smaller than previous studies on the same species Kien et al 2008;Wei et al 1997) as well as other species (Jacques 2004;Zhu et al 2008;Zhu et al 2009). The most suitable range of basic density for pulpwood in eucalyptus is 0.48 to 0.57 g • cm -3 and pulp yield decrease sharply when basic density falls below 0.4 exceeds 0.60 (Dean 1995;Ikemori et.…”
Section: Comparison Between Pilodyn Penetration and Wood Propertiescontrasting
confidence: 45%
“…Bending tests, as well as acoustic methods, are the most common technologies (e.g. Koizumi and Ueda 1986;Jacques et al 2004;Matheson et al 2008). For example, Koizumi et al (1990b) used a bending test device in a half-sib progeny trial of Japanese larch to estimate heritability of stiffness.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Koizumi et al (1990b) used a bending test device in a half-sib progeny trial of Japanese larch to estimate heritability of stiffness. More recently, Jacques et al (2004) andFujimoto et al (2006) have tested acoustic methods on standing trees to estimate MOE heritability in clonal and progeny trials of hybrid larch (L. x eurolepis and Larix gmelinii x L. kaempferi, respectively).…”
Section: Introductionmentioning
confidence: 98%
“…These studies also reported that the velocities obtained using TOF were higher than those obtained using longitudinal resonance [237][238][239] and flexural resonance. 235,237,240,241 Others have reported that TOF measured dynamic MOE values for timber samples were higher than static MOE values calculated using bending tests on these samples. 185,186,208,235,237,242,243 Hassan et al reported that dynamic MOE obtained using flexural vibration, longitudinal vibration, and ultrasound (TOF) where greater than those of static MOE values by 13.8, 22.3, and 30.9%, respectively.…”
Section: Variation In Stiffness From Pith To Bark Explanationmentioning
confidence: 99%